Effect of Anthropometric, Socioeconomic, and Behavioral Factors on Early Childhood Dental Caries in Tehran: A Structural Equations Modeling Approach - Maryam Mousavi; Mohammad Javad Kharazifard; Mir Saeed Yekaninejad; Abbas Rahimi Foroushani (Islamic Dental Association of Iran, 2017)
Background and Aim: Identification of the factors that affect early dental caries has an important role in health planning in different societies. This study was conducted to evaluate the effect of different factors on early caries in deciduous teeth. Materials and Methods: This cross-sectional study was conducted on 603 children aged 3-5 years in Tehran during 2013-14. Multistage stratified random sampling was done in the northern, southern, eastern, and western regions of Tehran. Data were collected by dental examination and by using a questionnaire answered by the parents. The Poisson regression analysis was used for evaluating the correlation between the independent variables and the results, while the structural equation modeling (SEM) method was applied to evaluate the joint effect of these factors on dental caries indices. Results: The mean and standard deviation (SD) of the decayed-missing-filled-teeth (dmft) and decayed-missing-filled-surfaces (dmfs) were equal to 6.45±4.02 and 11.62±10.61, respectively. The effects of body mass index (BMI) and the latent varia-bles of poor eating habits and oral hygiene on the dmft and dmfs were significant (P<0.05). The effect of the household socioeconomic status, as a latent variable, on the caries indices was not significant (P=0.29). Among the variables, poor eating habits had the greatest effect on the dmft (total standardized value=0.31) and dmfs (total standardized value=0.33). Conclusion: Dental caries is associated with poor eating habits, oral hygiene, and BMI. These factors can be modified and corrected through public health approaches such as providing counseling services, defining the principles of health behaviors, and teaching proper eating habits to parents and children.